THE AESTHETIC OF DHARMA: LITERARY PATHWAYS TO VIRTUE IN HINDU TEXTUAL TRADITIONS - I Wayan Artayasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study examines the aesthetic embodiment of dharma—the moral and cosmic law—in Hindu literary traditions. It explores how classical and vernacular texts such as the Ramayana, Mahabharata, Kakawin Arjunawiwaha, and Geguritan Dharma Prawerti articulate ethical and spiritual ideals through poetic beauty. Hindu literature is not merely a cultural artifact but a moral pedagogy that teaches virtue (śīla) through aesthetic experience. By employing hermeneutic and qualitative textual analysis, this paper demonstrates that aesthetic expression in Hindu literature transforms philosophical doctrines into lived moral consciousness. The study reveals that the literary presentation of dharma functions as a transformative pathway toward virtue, emotional refinement, and spiritual liberation (moksha).